Creating Relevancy in Agricultural Science Information: Examining the Impact of Motivational Salience, Involvement and Pre-Existing Attitudes on Visual Attention to Scientific Information - Laura Morgan Fischer; Courtney Meyers; R. Glenn Cummins; Courtney Gibson; Mathew Baker (Journal of Applied Communications, 2020)
Agricultural communications literature has indicated scientists are struggling to make information salient to consumers. Prior studies have examined the efficacy of message frames and types of appeals that increase visual attention and information processing among general consumers. Research suggests that value-oriented frames may connect with consumers through increased personal involvement and motivational salience. To evaluate the effects of competing message frames on visual attention, an eye-tracking experiment was conducted to understand the interaction between pre-existing attitudes and issue involvement on participants’ attention to messages about genetic modification and antibiotic use in livestock. For products that are low in issue involvement (i.e., food products and scientific information), the results indicated the reader devoted more time to reading advertisements that were framed to be more motivationally salient (i.e., the value-oriented frame). Because selective attention is the first part in the sequence of how individuals process information and form attitudes, agricultural science communicators should highlight values and motivational salience in their messaging. Recommendations for practitioners and the use of eye tracking as a research tool are described.
Keywords: Advertorials; Motivation; Salience; Value-Oriented; Visual Attention Allocation